(NrADIOAKTIWNOSTX (B/s - (NzABORENKO(B, (Nk(B.(Nbs; (NbARANOW(B, (Nw(B.(Ni(B.s ((NmOSKWA (B:s (NgOS(B. (NIZD(B.-(NWO TEHNIKO(B-(NTEORET(B. (NLIT(B.,s, 1953)
(NzAKL(B.: (NS(B. 63-64s
Keywords: (NrADIOAKTIWNOSTXs